ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH DI KABUPATEN KLATEN - Yektiningsih, Chucu Khotijah; Sarwono, Aris Eddy; Harimurti, Fadjar (Universitas Slamet Riyadi, 2021)
The purpose of this study was to analyze the magnitude of theeffectiveness, contribution, efficiency of hotel tax, restaurant tax and parking taxon local original income in the 2015-2019 Klaten district. The scope of thisresearch is the scope of the research carried out in Klaten Regency, the form ofthis research is an empirical study, namely by studying and studying the problemsor circumstances on the research object. The object of this research is the BPKDOffice in Klaten Regency. The researcher chooses the object because all data canbe obtained accurately from the relevant government institution. The populationdetermined in this study is the Budget Register Report and Realization of KlatenRegency Revenue for Fiscal Year 2015-2019. The sample used is the entirepopulation determined by researchers, namely the Budget Register Report andRealization of the Original Revenue of the Klaten Regency Fiscal Year 2015-2019, namely hotel taxes, restaurant taxes and parking taxes. Data collectiontechniques using secondary data. Data analysis techniques using effectivenessanalysis, contribution analysis and efficiency analysis. The results of the hotel taxanalysis, restaurant tax and parking tax reach effectiveness on local revenue. Theresults of hotel tax analysis, restaurant tax and parking tax reach efficienciestowards local own-source revenues. The results of the hotel tax analysis,restaurant tax and parking tax did not contribute to the region's original income.